Practical aspects of insulin administration: what the healthcare provider knows. Issue 3 (2nd September 2022) - Parker, Nousheen; Coetzee, Ankia; van Wyk, Lourentia; Conradie, Magda
Abstract : Background: Diabetes self-management education (DSME), a prerequisite for diabetes care, is mostly unstructured and inaccessible in the public health sector in South Africa (SA). Patient education is often delivered by healthcare professionals (HCPs) with limited time and proficiency, resulting in preventable errors with insulin administration. A study was undertaken to assess the knowledge of HCPs on the practical aspects of insulin administration and it was hypothesised that their expertise was insufficient. The unmet needs of DSME often transpire when preventable errors with insulin administration become clinically evident at higher levels of care. Methods: A prospective, descriptive study of HCPs' knowledge before and after attending a 'Diabetes 101' workshop was performed. Four workshops at Tygerberg Hospital (TH) and Worcester Provincial Hospital (WPH) were assessed between 2016 and 2019. A total of 146 participants completed a questionnaire before and after the workshops. Knowledge was scored on the correct responses per question and overall. The mean pre- and post-test scores were compared using two sample t-tests. Chi-square tests were used to analyse differences between pre- and post-training responses. Results: Of 146 participants, the majority were medical doctors ( n  = 116; 80%), mostly junior ( n  = 75; 65%) with 21% nursing practitioners. Before training there were significant deficiencies identified with only 3 of the 19 question items answered correctly by more than 50% of HCPs. The greatest knowledge deficits were with regard to insulin re-suspension and the injection technique and priming of the insulin pen. Following training there was a significant improvement between the pre-test mean percentage score of 36.0% (15) and post-test mean percentage score of 68% (16) ( p  < 0.001). Conclusion: Knowledge on the practical aspects of insulin administration is insufficient amongst HCPs but improved after structured education. Further research is needed to assess the long-term retention of knowledge and the impact of knowledge translation into clinical care.